Aplikasi Cendawan Endofit terhadap Perkembangan Populasi Nematoda Radopholus similis pada Pisang Barangan - Lisnawita Lisnawita; Ahmad Rafiqi Tantawi; Mukhtar Iskandar Pinem (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2013)
Radopholus similis is a major constraint to banana production in the world including Indonesia and growers have relied on nematicides to manage yield losses. The use of endophytic fungi is one method that may reduce the need for nematicides, however little is known on the effective application method of endophytic fungi to control R. similis. The aim of this research was to find out an effective application method of endophytic fungi to reduce R.similispopulation on banana. Fifteen isolates of endophytic fungi originated from banana corm and root collected from banana plantation in North Sumatera were applied to Barangan cultivar by sowing and deeping methods. The isolates was contained of 11 isolates of Fusarium sp. (2BSTMHMM, 3ASTMHP, 5ASP, 1ASU, 4BSP, 4BJP, 5BKJP, 4BSU, 1BJP, 2 BSP, and 4BKJP) and 4 isolates ofTrichoderma sp. (2BSTMHP, 4BSTMHP, 2BSPH, and 2BSTMHH). All of these endophytic fungi were able to suppress the population of R. similis and they had potential to promote plant growth.